PERANAN WANITA PETANI PADI SAWAH DALAM MENINGKATKAN PENDAPATAN RUMAH TANGGA DI DESA SEI BELURU KECAMATAN MERANTI KABUPATEN ASAHAN PROVINSI SUMATERA UTARA - Panjaitan, Evi Handayani; Yulida, Roza; ', Yusmini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this research are to find out women farmer’s profile in Sei Beluru village, to analyze an income women farmer’s household, to analyze a contribution income women farmer’s from farmer’s and non farms to household income. These research used a survey method with purposive sampling as a sampling technique, the characteristic are women who have job as a farmer as their primary job, women who have been a housewife and still have husband then have their own farm. Respondent total of this research are 41 respondent. The result is, from charateristics, the age of women farmer’s are between 36-60 years old, with junior highschool graduate, and most of women farmer’s experience in farmer’s industry are during 7-34 years. Total average of household income’s women farmer’s are Rp.24.239.091/years that came from primary household and part time income’s husband, wife and child. Contribution income’s women farmer’s to family income is 9,94%. Keywords: Woman Role, Farmer, Family’s Income